Studi kasus asuhan keperawatan pada pasien pneumonia dengan diagnosa sekunder hypertensive hearth disease - Sriwiyati, Lilik; Christina, Tri Yahya; Safaruddin, Safaruddin; Andika, I Putu Juni (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Ikatan Sarjana Farmasi Indonesia (ISFI), 2025)
Background: Pneumonia is the leading cause of death among children under five years of age. In addition to infants, the elderly and individuals with weakened immune systems are also highly susceptible to pneumonia. The incidence of pneumonia in Indonesia is on the rise. The prevalence of pneumonia in Java Province remains quite high, warranting serious attention. Nursing care for patients with pneumonia is essential, given that this disease is quite serious and significantly impairs the patient’s ability to meet the body’s oxygen needs. Purpose: To analyze nursing care for patients with pneumonia and a secondary diagnosis of hypertensive heart disease, covering the assessment, establishment of nursing diagnoses, interventions, implementation, and evaluation. Method: This study is a descriptive-analytical study using a case study approach. The purpose of the study is to describe the implementation of nursing care for a patient with pneumonia and a secondary diagnosis of hypertensive heart disease. The subject of the case study was one patient with pneumonia. Data analysis was performed using descriptive analysis.. Results: A patient with pneumonia and a secondary diagnosis of hypertensive heart disease presented with signs and symptoms of shortness of breath, chest heaviness, palpitations, and weakness; blood pressure readings indicated stage 1 hypertension. ECG revealed sinus rhythm with first-degree AV block, alternating episodes of TAVB with junctional escape rhythm and multiple PJCs; blood gas analysis indicated compensated metabolic acidosis; the P/F ratio indicated mild respiratory failure; chest X-ray showed pneumonia; and the chest X-ray revealed cardiomegaly accompanied by aortosclerosis. Based on these findings, the nursing diagnoses were established as impaired gas exchange and decreased cardiac output. The established SLKI (Specific Nursing Interventions) were acid-base balance and increased cardiac output. The established SIKI (General Nursing Interventions) were respiratory monitoring and cardiac care. Conclusion: Following treatment of a patient with pneumonia and a secondary diagnosis of hypertensive heart disease, who presented with gas exchange abnormalities and reduced cardiac output, the patient was able to achieve acid-base balance and an increased cardiac output. Keywords: Hypertensive Heart Disease; Nursing Care; Pneumonia. Pendahuluan: Pneumonia merupakan penyebab kematian terbesar pada anak di bawah usia lima tahun. Selain pada balita, lansia dan individu dengan sistem imun yang rendah juga sangat rentan menderita pneumonia. Kejadian pneumonia di Indonesia menunjukkan adanya peningkatan. Prevalensi pneumonia di Provinsi Jawa masih cukup tinggi sehingga memerlukan perhatian serius. Asuhan keperawatan pada pasien dengan pneumonia sangat diperlukan mengingat penyakit ini cukup serius dan sangat mengganggu kemampuan pasien dalam memenuhi kebutuhan oksigen tubuh. Tujuan: Untuk menganalisis asuhan keperawatan pada pasien pneumonia dengan diagnosa sekunder hypertensive hearth disease mulai dari pengkajian, penegakan diagnose keperawatan, intervensi, implementasi dan evaluasi. Metode: Penelitian ini adalah jenis penelitian deskriptif analitik dengan pendekatan studi kasus. Tujuan penelitian untuk mengetahui gambaran pelaksanaan asuhan keperawatan pada pasien pneumonia dengan diagnose sekunder hypertensive hearth disease. Subyek studi kasus adalah satu pasien dengan pneumonia. Analisa data menggunakan analisis deskriptif. Hasil: Pasien dengan pneumonia dengan diagnose sekunder hypertensive hearth disease didapatkan tanda dan gejala sesak nafas, dada terasa berat, jantung berdebar-debar, tubuh terasa lemah, tekanan darah menunjukkan hipertensi derajat 1, EKG didapatkan Irama sinus dengan AV block derajat 1, alternating episode TAVB dengan irama lolos junctional dengan multiple PJC, analisa gas darah menunjukkan asidosis metabolic terkompensasi, P/F rasio menunjukkan gagal napas ringan, rontgen thorax menunjukkan pneumonia, thorax menunjukkan cardiomegaly disertai aortosclerosis. Berdasarkan data tersebut ditegakkan masalah keperawatan gangguan pertukaran gas dan penurunan cardiac output. SLKI yang ditegakkan adalah keseimbangan asam basa dan curah jantung meningkat. SIKI yang ditegakkan adalah pemantauan respirasi dan perawatan jantung. Simpulan: Setelah dilakukan perawatan pada pasien pneumonia dengan diagnosa sekunder hypertensive hearth disease dengan masalah pertukaran gas dan penurunan cardiac output, pasien mampu mencapai keseimbangan asam basa dan mencapai cardiac output yang meningkat. Kata Kunci: Asuhan Keperawatan; Hypertensive Hearth Disease; Pneumonia.